Pengaruh Video Interaktif Berbasis Aplikasi CapCut terhadap Pengenalan Makhraj Huruf Hijaiyah - S, Nopita; Wirman, Asdi (Lembaga Yasin AlSys, 2025)
This study is motivated by the low ability of children in letter recognition and the prevalence of media that do not adequately support the development of this skill. The use of the CapCut application to create interactive videos is seen as a solution to complement learning, as it offers an engaging and participatory method for children to learn the makhraj of Hijaiyah letters. The research aims to describe the effect of using CapCut-based interactive films on the recognition of Hijaiyah letter pronunciation at Wahana Harapan Bangsa 1 Kindergarten, Padang City. This quantitative study employed a one-group pretest–posttest design, involving all 26 students, with a sample of 14 Class B1 students selected through purposive sampling. Data were collected through a 10-item test and analyzed using the t-test and N-Gain test with the assistance of SPSS version 25. The t-test results showed a t-value of 14.612, greater than the t-table value of 2.131, with a significance level of 0.000 < 0.05, thus rejecting H₀. These findings indicate that the use of CapCut-based interactive videos has a significant effect on early childhood’s ability to recognize the points of articulation of Hijaiyah letters.